Correlações espaciais e temporais na amplificação e oscilação paramétrica - Huguenin, José Augusto Oliveira (2006)
This work is based on studies of patrametric frequency conversion. It is concentrated in two different systems: Spontaneous and stimulated cavity free parametric down conversion (PDC) and an optical parametric oscillator. Both systems use a laser beam to pump a non linear crystal to produce two new beams, called signal and idler. Studies about light beams carrying orbital angular momentum (OAM) are pre- sented, and the Laguerre-Gauss modes are also discussed. Two different methods are used to obtain these modes experimentally. One method employs holograms known as spiral zones plates (SZP).This method was used to observe OAM transfer in cavity free stimulated parametric down conversion. As we show, parametric amplification is subjec to conservation of the total topological charge. According to our results, the situation is somewhat more complicated in parametric oscillation, where cavity effects are important. Squeezing of signal and idler quadratures is presented. We also observed moiré fringes patterns when SZP's are superposed. These patterns present topological defects as those observed in optical vortices interference. This work motivated a new study about moiré fringe patterns in spatial quantum correlations of twin photons produced by spontaneous PDC.We observed the spatial beats, characteristic of moiré fringes, in the coincidence profile of the twin photons.